Smart power grid vulnerability analysis in composite system through power grid modelling - Shouvik kumar Samanta; Chandan kumar Chanda (Institute of Advanced Engineering and Science, 2021)
A though the number of traditional literature reviews most of the researchers in this area have concluded that modern intelligent electric network a referred standard new model which is considering for proposed power flow model analysis of smart power grid vulnerability through composite network. By the theorem of max-flow and complex power network theorems that are represented the advance vulnerability indices for pick out endangered lines of the smart grid network. In other hand, the power flow model and existing models simulation are examined on the IEEE 39-bus test model. The results of the simulation introduced that the proposed concept of grid model, estimation and the index application are more adequate in smart grid weakness power and efficiency analysis. In this paper briefly summarize the methods and probabilities of a vulnerability index which was explained in specific in references. Therefore, it is imperative to further implement new models and new tools so as to reach the novel state and moderate the huge or massive potential shutoff